Review of the Nearctic genus Wilcoxia James (Diptera: Asilidae: Stenopogoninae), with descriptions of three new species - Pollock, Darren A.; Reichert, Lisa A. (Zootaxa, 2019)
The robber fly genus Wilcoxia is revised based on external morphological features of adults. For each species the following is provided: type specimen information, diagnostic features, description, natural history including associated prey data, and geographical distribution (derived from georeferenced localities for both examined specimens and literature records). A key to adults of Wilcoxia, supplemented with photographs of habitus and selected morphological features, is included. The genus comprises eight species, distributed primarily in the southwestern United States. Three new species are described: W. apache (type locality: New Mexico, Quay County, Apache Canyon), W. flavipennis (type locality: Arizona, Pima County, Organ Pipe Cactus National Monument), and W. forbesi (type locality: New Mexico, Doña Ana County, 1 mi. NW Tortugas Mt.). There appear to be two reasonably well-defined species groups (cinerea and martinorum groups, with four species in each), based on structural features, seasonality and natural history. Identified prey items (for W. apache, W. forbesi and W. martinorum) include representatives from Hemiptera (eight families), Coleoptera (one family), Hymenoptera (five families) and Diptera (10 families). A discussion on the structural heterogeneity of Wilcoxia and a history of its classification are provided.